Comparative Study of Local Government Spending Efficiency in Achieving HDI Components Before and During the Covid-19 Pandemic - Muhammad Havizd; Roosemarina Anggraini Rambe (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to measure the efficiency of local government spending in achieving the human development index in each province in Indonesia before (2019) and during the COVID-19 pandemic (2020). The inputs used consist of four types of spending, which are spending per capita on the economy, health, education, and social protection. The outputs used are the three components in the human development index, namely life expectancy, average length of schooling, and real spending per capita. This research is a quantitative descriptive study using secondary data for 2019 – 2020. Data Envelopment Analysis (DEA) was applied using the Variable Return to Scale (VRS) approach. The efficiency model used is Output Oriented. The results of this study show that the average efficiency score of 34 provinces in Indonesia before the COVID-19 pandemic (2019) was 0.946; and during the COVID-19 pandemic (2020) it was 0.946. There were 6 provinces that were consistently relatively efficient both before and during the COVID-19 pandemic; they were provinces of Banten, DI Yogyakarta, Jakarta; West Java, Central Java, and North Sumatra. Meanwhile, there was one province that was efficient before the COVID-19 pandemic, but become inefficient during the pandemic, that is Riau Archipelago.